An Anlysis of Students’ Perspectives on the P5 Project Based on Local Wisdom of Traditional Weaving Southwest Maluku - Rumalewang, Pitra Aldo; Pattiasina, Johan; Soumokil, Agustinus; Telussa, Rivaldo Paul; Pattipeilohy, Poltjes (Honoli of Journal Primary Teacher Education, 2025)
This study aims to describe students' perceptions of the Pancasila Student Profile Strengthening Project (P5) integrated with West Southwest Maluku traditional weaving thru the themes of Sustainable Lifestyle and Local Wisdom. The research approach used is descriptive qualitative, with a research subject of 15 fifth-grade students from Kaiwatu Christian Elementary School. Data analysis techniques refer to the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research results show that after participating in the P5 project, students experienced a significant improvement in their understanding, attitudes, and skills. Students understand the importance of environmental protection by processing plastic waste into Ecobricks and integrating their creations with traditional woven fabric as a form of preserving local culture. This activity fosters environmental awareness, responsibility, cooperation, and a sense of pride in local culture. Additionally, this project fosters creativity, independence, and character in line with Pancasila values. Thus, the implementation of the P5 project based on Ecobrick and West Southwest Maluku traditional weaving is effective in shaping students' character to be faithful, of noble character, environmentally conscious, and with a strong cultural identity.